2020
DOI: 10.1186/s10194-020-01136-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, tolerability, and safety of erenumab for the preventive treatment of persistent post-traumatic headache attributed to mild traumatic brain injury: an open-label study

Abstract: Background: Calcitonin gene-related peptide (CGRP) has recently been implicated in the pathogenesis of posttraumatic headache (PTH), which raises the prospect for therapeutic use of monoclonal antibodies targeting CGRP or its receptor. Therefore, we decided to assess the efficacy, tolerability, and safety of erenumab for prevention of persistent PTH attributed to mild traumatic brain injury. Methods: A single-center, non-randomized, single-arm, open-label study of erenumab for adults aged 18-65 years with pers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 21 publications
0
40
0
Order By: Relevance
“…One recent open-label study reported promising data suggestive of CGRP antagonism having therapeutic benefit in prevention of persistent PTH. 12…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One recent open-label study reported promising data suggestive of CGRP antagonism having therapeutic benefit in prevention of persistent PTH. 12…”
Section: Discussionmentioning
confidence: 99%
“…8 Intravenous infusion of CGRP provokes migraine attacks in patients with migraine, 9,10 and CGRP antagonism has proven beneficial for the acute and preventive treatment of migraine. 11 In support of CGRP involvement in PTH, one open-label study found that CGRP antagonism might have therapeutic benefit in patients with persistent PTH, 12 and two animal studies reported findings suggestive of hypersensitivity to CGRP in concussed rodents. 13,14 Thus, it is timely to ascertain whether, and if so by what mechanisms, CGRP is involved in the genesis of persistent PTH.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, preclinical studies show that mechanisms involving CGRP drive TBI-related development of central sensitization as well as the response to bright light stress and may therefore be relevant for the expression of PTH ( 11 ). In line with these findings, erenumab, a monoclonal antibody targeting the CGRP receptor, has been shown to reduce headache intensity in PTH ( 12 ). These findings strongly support a role of CGRP in PTH.…”
mentioning
confidence: 73%
“…This finding may support the use of CGRP modulators in the acute and preventive treatment of PTH. If the mechanisms driving the persistent head pain in PPTH are shared with those of CM, then it is likely that a subgroup of patients with PPTH with a CM phenotype will benefit from these approaches [68].…”
Section: Clinical Models and Overlapmentioning
confidence: 99%
“…The role of CGRP monoclonal antibodies in PTH is being studied. Initial open-label shortterm evidence on the effectiveness of erenumab in PPTH with a predominant CM phenotype showed a meaningful response in 28% of the patients, which is lower than the responder rate that emerged from the CM studies in difficultto-treat populations [74][75][76]. Fremanezumab is being studied for the treatment for PTH in a phase 2 multicentre randomized controlled study (ClinicalTrials.gov Identifier: NCT03347188).…”
Section: Treatmentmentioning
confidence: 99%